Analysis Of Crude Palm Oil (Cpo) Quality Based On Vacuum Dryer Performance At Primajasa Palm Oil Mill - Agam Muarif; Rizka Mulyawan; Marisa Fitria (Fakultas Teknik Universitas Wahid Hasyim, 2022)
The products produced at the Primajasa Palm Oil Mill are Crude Palm Oil (CPO) and palm kernel (kernel). The palm oil processing process goes through several stations, including loading ramp station, sterilizing station, threshing stations, digesting and pressing station, clarification station, and kernel stations. In the palm oil processing industry, the main factors that can cause damage palm oil quality are high moisture content and free fatty acid (FFA) levels. This study aims to analyze the quality of CPO based on the performance of the vacuum dryer at the Primajasa Palm Oil Mill as seen from the free fatty acid (FFA) and moisture content. The average results obtained from the analysis of the moisture content of CPO before entering the vacuum dryer and after leaving the vacuum dryer were 0.57% and 0.27%. Meanwhile, the average results obtained from the analysis of FFA CPO levels before entering the vacuum dryer and after leaving the vacuum dryer were 3.63% and 3.57%. Based on these results, it is known that a vacuum dryer can reduce the value of moisture content and FFA levels contained in CPO. These results also indicate that the moisture content and free fatty acid (FFA) content in the sample are in accordance with the national quality standard of CPO.